EFFECT OF VARIOUS ORGANIC SUPPLEMENTS ON NONENZYMATIC ANTIOXIDANT AND MINERALS EXPRESSION IN CALOCYBE INDICA - K. SHARMA, SATISH; LALL, M. ALOK; LAL, A. ABALISHA (The Bioscan, 2013)
Maintenance of equilibrium between free radical production and antioxidant defences is an essential condition for normal organism functioning. The intonation of the mushroom used now-a-days in the field of medicine, is the way where this is moderately achieved. In this regard the nutritional values of Calocybe indica which is popular among the cultivated mushrooms have been determined. The results showed that Calocybe indica were rich in non-enzymatic antioxidant and minerals. It is clear from the results that all the organic supplements added in the substrate at the time of spawning, showed higher concentrations of non-enzymatic antioxidant and minerals as compared to control. This study revealed the presence of non-enzymatic antioxidant in the samples and the striking feature of present work is to maximize the usage of mushroom in the powdered form when there is certain unstable condition for the usage of mushroom in the fresh form.